Angiogenesis in ocular and extraocular sebaceous carcinoma - Toberer, Ferdinand; Hänßle, Holger; Enk, Alexander; Hartschuh, Wolfgang; Bertlich, Ines; Hartmann, Julia; Helmbold, Peter (Acta dermato-venereologica, 2019)
To shed more light on the pathogenesis of sebaceous carcinoma, we analysed the expression of proteins related to angiogenesis in 18 ocular and 22 extraocular sebaceous carcinomas using a broad panel of immunohistochemical markers. To quantify the expression of D2-40, vascular endothelial growth factor, vascular endothelial growth factor receptor-2 and -3, we calculated a quantification score by considering the percentage of positive tumour cells (0=0%, 1=up to 1%, 2=2-10%, 3=11-50%, and 4=>50%) in relation to the staining intensity (0=negative, 1=low, 2=medium, and 3=strong). Additionally, lymphatic microvessel density in the D2-40 stained sections was counted. Vascular endothelial growth factor receptor-3 (quantification score 9.42 ± 2.94) was significantly more strongly expressed than vascular endothelial growth factor receptor-2 (quantification score 2.15 ± 2.42, p < 0.001). Furthermore, epidermal vascular endothelial growth factor expression was negatively correlated with the intratumoural lymphatic vessel density, and the ratio of small lymphatics to large lymphatics was much higher in intratumoural tissue than in paratumoural tissue and in intraindividual control tissue, suggesting a lymphangiogenetic potential of sebaceous carcinoma.
Gesehen am 04.02.2020